2023
DOI: 10.1161/strokeaha.123.043551
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Loss of Chromosome Y Is Associated With Functional Outcome After Ischemic Stroke

Malin Dorvall,
Annie Pedersen,
Jan P. Dumanski
et al.

Abstract: BACKGROUND: Mosaic loss of chromosome Y (LOY) is associated with cardiovascular and neurodegenerative diseases in men, and genetic predisposition to LOY is associated with poor poststroke outcome. We, therefore, tested the hypothesis that LOY itself is associated with functional outcome after ischemic stroke. METHODS: The study comprised male patients with ischemic stroke from the cohort studies SAHLSIS2 (Sahlgrenska Academy Study on Ischemic Stroke Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The basic premise of our study is the concept of aberrant clonal expansions of cells in morphologically normal tissues [ 45 ] and this is best studied in the hematopoietic system. It is termed clonal hematopoiesis [ 57 , 58 ], where the most prevalent alteration is LOY, a mutation also linked to various diseases in men [ 6 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. These aberrant clonal expansions have also been described in solid tissues, often in connection with cancer, and are commonly referred to as field cancerization [ 46 , 47 , 48 , 49 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic premise of our study is the concept of aberrant clonal expansions of cells in morphologically normal tissues [ 45 ] and this is best studied in the hematopoietic system. It is termed clonal hematopoiesis [ 57 , 58 ], where the most prevalent alteration is LOY, a mutation also linked to various diseases in men [ 6 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. These aberrant clonal expansions have also been described in solid tissues, often in connection with cancer, and are commonly referred to as field cancerization [ 46 , 47 , 48 , 49 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dysregulation of autosomal gene expression in leukocytes with LOY in a pleiotropic fashion affects many of their immune cell functions [ 18 ]. Numerous studies have also shown a strong association between hematopoietic LOY and all-cause mortality [ 6 , 20 ] as well as an increased prevalence or poor outcome of many diseases in males, for instance, cardiovascular disease [ 21 , 22 ], Alzheimer’s disease [ 16 , 23 ], stroke [ 24 ], COVID-19 [ 25 ] and multiple types of cancer, among them BLCA [ 6 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 In brief, patients with first-ever or recurrent acute ischemic stroke aged 18–69 years were recruited between 1998 and 2003. For validation, a second observational longitudinal cohort study, the SAHLSIS phase 2 ( SAHLSIS2 ), 5 was used. This ongoing study includes first-ever or recurrent adult cases with acute stroke of all ages, and this study includes participants recruited during the period 2015–2020.…”
Section: Methodsmentioning
confidence: 99%
“…45,46 In cardiovascular diseases, it has been reported as an adverse prognostic factor in some conditions, such as cerebral infarction and post-transcatheter aortic valve replacement. 47,48 Although studies on the association and mechanisms of mLOY with the development of HF are limited, Sano et al suggested the following possibilities. 49 The mice model with mLOY showed myocardial fibrosis, and the myocardial macrophages, induced by the loss of Y, were found to be in an activated inflammatory state.…”
Section: Mosaic Loss Of Y Chromosomementioning
confidence: 99%